Adult education programmes in community centres - Trinidad and Tobago. Ministry of Planning and Development (Ministry of Planning and Development, 1970)
This paper gives the objectives of the Third Five Year Development Plan in respect of adult education over the plan period, 1969-1973. It gives a brief history of the existing community centres and the adult education programmes held at these centres. It is concluded that in spite of the full programmes at the centres, there is still a great deal of unused capacity existing at some of them. Suggestions are made for where greater emphasis should be placed
Keywords: Adult education programmes